Crosslinked Polyimide and Reduced Graphene Oxide Composites as Long Cycle Life Positive Electrode for Lithium‐Ion Cells. Issue 20 (2nd September 2020) - Gao, Hui; Tian, Bingbing; Yang, Haofan; Neale, Alex R.; Little, Marc A.; Sprick, Reiner Sebastian; Hardwick, Laurence J.; Cooper, Andrew I.
Abstract: Conjugated polymers with electrochemically active redox groups are a promising class of positive electrode material for lithium‐ion batteries. However, most polymers, such as polyimides, possess low intrinsic conductivity, which results in low utilization of redox‐active sites during charge cycling and, consequently, poor electrochemical performance. Here, it was shown that this limitation can be overcome by synthesizing polyimide composites (PIX) with reduced graphene oxide (rGO) using an in situ polycondensation reaction. The polyimide composites showed increased charge‐transfer performance and much larger specific capacities, with PI50, which contains 50 wt % of rGO, showing the largest specific capacity of 172 mAh g −1 at 500 mA g −1 . This corresponds to a high utilization of the redox active sites in the active polyimide (86 %), and this composite retained 80 % of its initial capacity (125 mAh g −1 ) after 9000 cycles at 2000 mA g −1 . Abstract : Live long and prosper : Composites of reduced graphene oxide and a three‐dimensional polyimide with electrochemical redox active groups are synthesized and used as positive electrodes in lithium‐ion batteries. The composites show higher specific capacity (125 mAh g −1, 2000 mA g −1 ) and longer cycling life (80 % retention after 9000 cycles) than the polyimide on its own.